Law, love and violence: Interfaith romance in modern Egypt - El-Maghlawy, Mariam (AUC Knowledge Fountain, 2019)
For the past few decades, many incidents of sectarian violence have been triggered by rumors of interfaith sexual and romantic relationships between Muslims and Coptic Christians in Egypt. This thesis argues that the ways in which the Egyptian modern state chooses to govern women’s bodies and address the Coptic question has inevitably enabled sectarian violence witnessed today to take on its current form. One of the main implications of the modernization of the Egyptian legal system was the state’s ability to “jam” women, family, sexuality and religion into the private sphere, as opposed to the public sphere. This essentially has created a form of “cross-contamination” in which the religious came to appropriate the family, and the family acquired the quality of the religious. To that end, this thesis tells the story of the “affective, visceral, corporeal workings of everyday state power” that coheres that cross-contamination between the spheres of the family and religion. Through using the tools offered to it by modernity, the Egyptian modern state has been able to maintain a similar religious hierarchy to that which existed in the Ottoman era, only this time it has confined this religious hierarchy almost exclusively to the domain of the family. One of the main outcomes of such an arrangement is that political conflicts over religious difference often end up unfolding over the terrain of familial and sexual relationships. By regulating love, the state has concretized the conservatism of both the Muslim and Coptic communities and has produced a space for sectarian violence over women’s bodies, sexuality and romance.